ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG PASAR KIDUL KABUPATEN BANGLI - Sang Ayu Made Dwi Marheni; I Wayan Priyana Agus Sudharma (Universitas Udayana, 2025)
The income of traditional market traders is influenced by various factors that affect theireconomic well-being. This study aims to analyze the simultaneous and partial effects of educationlevel, age, business duration, and business location on the income of traders at Pasar Kidul, BangliRegency. The sample used in this study consists of 90 traders at Pasar Kidul. The analyticaltechnique employed is inferential descriptive analysis using Multiple Linear Regression with theaid of SPSS 26 software. The obtained coefficient value is 0.719, with a determination value of71.9%. This indicates that the income of Pasar Kidul traders (Y) is explained by 71.9 percentthrough the variables of Education Level (X1), Age (X2), Business Duration (X3), and BusinessLocation (X4), while the remaining percentage is explained by other variables not included in themodel or study.The analysis results show that the variables of education level, age, business duration, andbusiness location simultaneously have a significant effect on the income of traders at PasarKidul. Partially, the variables of education level, business duration, and business location have apositive and significant effect on traders' income, while the age variable does not significantlyaffect the income of traders at Pasar Kidul.keyword: income, education, age, length of business, business locationKlasifikasi JEL: D31, L81, R12